Chemistry and Technology for Large-scale Synthesis of Graphene Nanoplatelets - Melezhyk, Alexander (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To determine the synthesis conditions under which it would be possible to obtain high-quality graphene nanoplatelets (GNPs) on a large scale. Materials and Methods: The ability of graphite for cold expansion and exfoliation was found to depend on the degree of defectiveness of its crystal structure. Highly defective graphite structures are not prone to intercalation, exfoliation, and expansion, whereas perfect ones can be transformed more easily, which is important when setting up a large-scale pilot production of graphene-based nanomaterials. Results and Discussion: It is assumed that for efficient exfoliation of graphite materials, the power of ultrasonic radiation should be above a certain threshold value, whereas the concentration of that power in the working volume of the flow-through chamber and the contact time for the treated solution in that chamber should also exceed certain thresholds values. Conclusion: Furthermore, the following stages are proposed to transform the expanded graphite intercalation compound (EGIC) particles into GNPs: (1) Irreversible separation of worm-like EGIC particles into coarse GNPs and tight aggregates thereof, (2) irreversible separation of those GNPs and aggregates into thin GNPs and tight aggregates thereof, (3) irreversible separation of the tight GNP aggregates into smaller-size ones and individual thin GNPs, (4) reversible transformation of the coarse GNPs into exfoliated ones, and (5) reversible formation and decomposition of weak thin GNP aggregates. The efficiency and direction of those transformations were found to depend on the power of the ultrasonic radiation and the concentration of the processed graphite material.